Uji Aktivitas Antibiofilm Ekstrak Daun Binahoang (A. Cordifolia) Terhadap Bakteri Staphylococcus Aureus - Niki Vina Ngaeni; Yusuf Eko Nugroho; Ira Pangesti (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
One of the natural ingredients that is utilized as a medicinal ingredient is the binahoang plant. Binahoang has roots, leaves, tubers, stems, flowers that contain active compounds namely flavonoids, alkaloids, torpenoids, and saponins. The purpose of this research is to determine whether binahoang leaf extract can inhibit the growth of Staphylococcus aureus bacterial biofilm. The research method used is True Experimental Design. This research design uses Posttest Only Control Deisgn. Where there are three groups, namely the treatment group, positive control group and negative control group. The data obtained will be tested statistically using the JASP v.18 analysis of variance method and followed by the Paired Sample T-test parametric test. The results of this research obtained that binahoang leaf extract is able to inhibit biofilm against Staphylococcus aureus bacteria with an average value in the biofilm formation inhibition activity test in 3 treatments namely 0.372; 0.441; 0.314 and positive control 0.610. So it can be stated that the results of bacterial growth in the treatment have a smaller value than the positive control of tetracycline 0.03 mg/ml. The conclusion of this research is that binahoang (A. cordifolia) leaf extract can inhibit biofilm growth against Staphylococcus aureus bacteria.